The students’ activity profiles and mathematic problem solving ability on the LAPS-Heuristic model learning - Amidi, Amidi; Zahra, Farah Anisah (Unnes Journal of Mathematics Education, 2018)
Problem-solving skills that cover the ability to understand problems, design mathematical model, complete the model and interpret the solution obtained are the abilities which students must possess. With regard to above symptom, this study described student’s activity and mathematics problem solving ability based on SOLO Taxonomy on Laps-Heuristic learning model. The procedure of the study was done through providing learning with Laps-Heuristic model with mind mapping, observing student activity during learning, giving mathematics problem solving test, analyzing the result of mathematics problem solving test, classifying the result of mathematics problem solving test based on taxonomy of SOLO, choosing the subjects of study, interviewing selected subjects, and compiling the study results. While the procedures of data analysis of this study included data reduction, data presentation, and conclusion. Based on the result of the study, it showed that the students’ activity was excellent due the fact that their scores were above 75% and their problem solving abilities were classified based on the SOLO Taxonomy consisting of 8 relational level students, 25 multi-structural level students, and 1extended abstract student.